1996
DOI: 10.1111/j.1749-6632.1996.tb56257.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypochondroplasia: Molecular Analysis of the Fibroblast Growth Factor Receptor 3 Gene

Abstract: Hypochondroplasia is an autosomal-dominant, human skeletal dysplasia with features similar to, but milder than those found in achondroplasia. Although thought to be relatively common, a comprehensive determination of its incidence and prevalence has not been published. It is thought that many mildly affected individuals do not seek medical intervention and may be difficult to distinguish from individuals with short stature but without skeletal dyspla~ia.~ Most cases of hypochondroplasia occur sporadically as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Incomplete screening may explain the 70% detection rate for FGFR3 mutations in HCH It has been reported that about 30% of HCH cases do not have a mutation in FGFR3 (Prinos et al 1995;Bellus et al 1996;Rousseau et al 1996a,b,c;Fofanova et al 1998;Prinster et al 1998;Ramaswami et al 1998). We found that p.Asn540Lys, p.Gly380Arg, and p.Lys650Gln mutations in FGFR3 together account for about 90% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete screening may explain the 70% detection rate for FGFR3 mutations in HCH It has been reported that about 30% of HCH cases do not have a mutation in FGFR3 (Prinos et al 1995;Bellus et al 1996;Rousseau et al 1996a,b,c;Fofanova et al 1998;Prinster et al 1998;Ramaswami et al 1998). We found that p.Asn540Lys, p.Gly380Arg, and p.Lys650Gln mutations in FGFR3 together account for about 90% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the proximal tyrosine kinase domain (N540K) give rise to an even milder disorder called hypochondroplasia. (13) The most severe of these syndromes is the neonatal, lethal TDII (K650E), which is caused by a mutation in the kinase activation loop. (14) It is intriguing that the cysteine substitutions at residues 370 -371 and 373 lead to the lethal TDI and the nearby G375C mutation results in the less severe achondroplasia.…”
mentioning
confidence: 99%
“…1620C>A and 1620C>G mutations which lead to Asn540Lys aminoacid substitution are detected in approximately 50-70% of affected individuals (4). Codon 540 in exon 13 is a major hotspot (7). The other mutations of this gene account for fewer than 2% of HCP patients (8).…”
Section: Discussionmentioning
confidence: 99%